INTRODUCTION TO “THE HEBREW INSCRIPTIONS FROM SARDIS” - Mitten, David Gordon (Harvard theological review, 2002)
Five of these inscriptions on stone in Hebrew were excavated in the Roman synagogue at Sardis, sixty miles northeast of Izmir in Turkey, during the excavation seasons of 1962 and 1963; the sixth is a stray find from near the Temple of Artemis. Other Hebrew inscriptions or joining fragments may well lurk in the piles of hundreds of marble revetment pieces stored in the depots outside of the north wall of the synagogue.